Tensile and superelastic behaviors of Ti-35Nb-2Ta-3Zr with gradient structure. (September 2020) - Wang, Liqiang; Wang, Yingchen; Huang, Wei; Liu, Jia; Tang, Yujin; Zhang, Ling; Fu, Yuanfei; Zhang, Lai-Chang; Lu, Weijie
Abstract: We investigated the tensile and superelastic behaviors of Ti-35Nb-2Ta-3Zr processed by double-faced friction stir processing that results in a roughly 2 times higher yield strength with an elongation of 37%. The friction stir processed specimens exhibited different superelasticity as loading cycle increased. To assess the strength and deformation of gradient structure, in situ micro compression tests were conducted on stir zone and heat affected zone, revealing higher strength in stir zone and better ductility in heat affected zone. The combination of stir zone and heat affected zone could increase the strength and maintain the ductility of the specimen simultaneously. Graphical abstract: Unlabelled Image Highlights: Ti35Nb2Ta3Zr processed by double-faced friction stir processing obtained roughly 2 times higher yield strength. Superelasticity showed different tendency after friction stir process. Higher strength in stir zone and better ductility in heat affected zone were confirmed by in situ microcompression tests.